KOMPARASI HASIL BELAJAR MATEMATIKA ANTARA SISWA YANG DOMINAN BERGAYA BELAJAR VISUAL, AUDITORIAL, DAN KINESTETIK DI SDN GUGUS III KECAMATAN LAMONGAN - Siska Aryani Sekarwati; Moh Edy Nurtamam (Program Studi Pendidikan Guru Sekolah Dasar, 2018)
ABSTRACTThis research purpose to know the comparison of mathematic learning outcomes between students who dominant style visual, auditorial, and kinesthetic learning. This research was conducted in class V elementary school of cluster III Subdistrict Lamongan. This research is a quantitative reasearch with the type of comparative research. Population in this research were all students of class V in elementary school of cluster III Subdistrict Lamongan.Technique sampling used purposive sampling. Data analysis using ANOVA test and continued with Scheffee test. The results of research: result of the hypothesis test using ANOVA test, show that Fcount= 5,674 Ftable=3,07 so, Ho is rejected, which means there is a significant difference of mathematic learning outcomes between students who dominant style visual, auditorial, and kinesthetic learning in elementary school cluster III Subdistrict Lamongan. Further test with Scheffe test, it show that there is no significant difference of mathematics learning outcomes between student dominant style of visual learning with student dominant style of auditorial learning, there was a significant difference of mathematics learning outcomes between student dominant style of visual learning with student dominant style of kinesthetic learning, there was no significant difference of mathematics learning outcomes between student dominant style of auditorial learning with student dominant style of kinesthetic learning. Keywords : Mathematic Learning Outcomes, Visual Learning Style, Auditorial Learning Style, Kinesthetic Learning Style ABSTRAKPenelitian ini bertujuan untuk mengetahui perbandingan hasil belajar matematika antara siswa yang dominan bergaya belajar visual, auditorial, dan kinestetik. Penelitian ini dilakukan di kelas V SDN Gugus III Kec. Lamongan. Teknik pengumpulan data menggunakan angket dan dokumentasi. Populasi pada penelitian ini adalah seluruh siswa kelas V SDN Gugus III Kec. Lamongan. Analisis data menggunakan uji ANOVA dan dilanjutkan dengan uji Scheffee. Hasil penelitian: hasil uji hipotesis menggunakan uji ANOVA menunjukkan bahwa Fhitung= 5,674Ftabel = 3,07 sehingga Ho ditolak, yang berarti ada perbedaan yang signifikan hasil belajar matematika antara siswa yang dominan bergaya belajar visual, auditorial, dan kinestetik di SDN Gugus III Kec. Lamongan. Uji lanjut dengan uji Scheffee yaitu tidak ada perbedaan yang signifikan hasil belajar matematika antara siswa yang dominan bergaya belajar visual dengan siswa yang dominan bergaya belajar auditorial, ada perbedaan yang signifikan hasil belajar matematika antara siswa yang dominan bergaya belajar visual dengan siswa yang dominan bergaya belajar kinestetik, tidak ada perbedaan yang signifikan hasil belajar matematika antara siswa yang dominan bergaya belajar auditorial dengan siswa yang dominan bergaya belajar kinestetik